Theoretical and Judicial Aspects of Judicial Practice Regarding the Offense of Concealment. Comparative Study with Money Laundering and Favoring the Perpetrator: Array - Ionescu Dumitrache, Ana Alina (Acta Universitatis Danubius. Juridica, 2021)
This article analyzes the relevant aspects regarding the content of the crime of concealment, a crime that endangers the social values regarding the administration of justice and patrimony. The study also includes relevant examples from judicial practice regarding the constitutive content of this crime. There are also analyzed the main elements that distinguish the crime of concealment from the crime of money laundering and that of favoring the perpetrator.